Condition dependence of shared traits differs between sympatric Anolis lizards. Issue 2 (29th May 2017) - Curlis, John David; Davis, Ryan William; Zetkulic, Emily; Cox, Christian L.
GRAPHICAL ABSTRACT: A sexual signal (dewlap size) and a combat trait (jaw width) were correlated with condition in only one of two anole lizards in this study, suggesting that linkage between energetics and sexually selected traits varies among closely related species. Abstract: In many species, sexually selected combat and display traits can confer dramatic fitness benefits to males by aiding in mate acquisition, so individuals maximally invest energy into their growth and maintenance. Such traits are deemed condition‐dependent, as the energy that is available for investment depends on the health and condition of the individual. Condition dependence is present in a wide range of traits across many taxa, but the extent to which condition dependence varies among shared traits in closely related species is poorly understood. We tested for condition dependence in two Anolis lizards, the ground anole ( Anolis humilis ) and the slender anole ( Anolis limifrons ). Specifically, we measured dewlap area, jaw length, jaw width, and sprint speed, and then regressed one of two indices of body condition on each of these traits for both species. We found that dewlap area and jaw width exhibited condition dependence in ground anoles, but not in slender anoles. Sprint speed and jaw length were not condition‐dependent in either species. The presence of condition dependence in ground anoles, but not slender anoles, implies evolutionary liability in the condition dependence of shared traits. Additionally, the fact that condition dependence was only detected in ground anoles, which have a greater relative dewlap size, suggests a potential role for signal evolution or strength of sexual selection in the evolution of condition dependence. Finally, our research suggests that variation in condition dependence of sexually selected traits could have implications for the evolution of dewlap diversity among Anolis species.